Strategi Dakwah Guru SMA Plus Negeri 17 Palembang dalam Membina Akhlak Siswa di Asrama Tahun Ajaran 2017/2018 - Hamidah Hamidah; Manalullaili Manalullaili; Alham Irvani (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2017)
This research was conducted to explain and straighten about the view of the community on the image of boarding schools that are less good in some communities carried out in the cottage messagerenren Ar_Riyadh 13 Ulu Palembang.Karena as the development dzaman and the development of world of technology increasingly sophisticated, the parents began to smarter in choosing educational institutions for his son. However, there are some people who are not paying attention and give attention to their children so that the boarding school is suitable for their children so that the community indirectly assume that boarding school as a daycare and place of naughty children. Therefore the thesis that the researcher created entitled "Public Relations Strategy In Straightening People's View Of Image Pondok Pesantren Ar-Riyadh 13 Ulu Palembang" The problems in this study are: How Strategies Conducted Public Relations Pondok Pesantren In Straightening People's Views Against Ar-Riyadh Boarding House 13 Ulu Palembang? How is the performance of Ar-Riyadh boarding school public relations? This research uses qualitative research methods. Data collection was obtained based on interviews, observation and documentation. While to analyze data using descriptive qualitative research method. Descriptive study is part of qualitative research that seeks to describe a phenomenon, events, events that will occur now. With the aim to find out how the performance of public relations is being run and what causes the occurrence of problems faced by public relations itself.